Poetics of Descent in Colombian Caribbean Poetry (2017)
The poetry of the Colombian Caribbean contains several recurrent themes pertaining to this region: mestizaje , hybridity, cosmopolitanism, neoregionalism, “laric poetry” [poesía lárica ], identity, other - ness, orality. This paper examines the way in which several poets of the Colombian Caribbean (José Ramón Mercado, Meira Delmar, Jorge García Usta, Gabriel Ferrer, and Raúl Gómez Jattin) develop a poetics of descent , celebrating the conjunction of the epic and the mythical, sacrality and death, where the epic is understood as “mythical narration of lived experience”, founded on descent as a category for valuing the other, including the family and friends, in death or the celebration of life. These poets also reveal a “laric poetry” or poetry of the home and loved ones: which includes landscapes and the time of memory, identity of place, but also elegy. In these poems, memory is not tragic, but nostalgic. Memory is conjugated as specific remembrance, as a song to that which no longer exists; “flowered memory” of the absent image